PENGARUH PENAMBAHAN GLISEROL DAN LILIN LEBAH PADA SUSUT BERAT BUAH SAWO KHAS BANTEN - Nufus Kanani; Ekasari Ekasari; Anas Subkhan; Wardalia Wardalia; Ranaldy Riky (Universitas Muhammadiyah Jakarta, 2018)
Packaging is a protection of food product to maintain the quality and durability of food. The aim of this study was to produce edible film as sapodilla fruit preservation, to get the optimum composition of glycerol and beeswax mixture and to get the optimum characteristics of edible film based on cassava peel starch. The methodology of this study was use 3 grams of cassava peel starch with glyserol consentration range 0,75 to 1.25% v/v and beeswax consentration range 1 to 3 w/v.The parameters tested were fruit weight loss, thickness, tensile strength, elongation percentage and solubility. The results showed that the lowest weight loss value were obtained on the addition of 0.75% glycerol and 3% beeswax which were 3.3% of weight loss in 7 days.